2013
DOI: 10.1371/journal.pone.0067400
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of DC-SIGN-Mediated Entry Pathway of Engineered Lentiviral Vectors in Target Cells

Abstract: Dendritic cells (DCs) are potent antigen-presenting cells and therefore have enormous potential as vaccine targets. We have previously developed an engineered lentiviral vector (LV) that is pseudotyped with a mutated Sindbis virus glycoprotein (SVGmu), which is capable of targeting DCs through Dendritic Cell-specific ICAM3-grabbing Nonintegrin (DC-SIGN), a receptor that is predominantly expressed by DCs. In this study, we aimed to elucidate the internalization and trafficking mechanisms of this viral vector sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…A recent study indicated that RV-G bound to an antibody transfected in a neuroblastoma cell line is targeted via early and late endosomes to lysosomes (58). In addition, lentiviral vector transduction of dendritic cells involved endosomal trafficking, and its efficiency was enhanced by suppressing autophagy (59). Indeed, we have recently reported an increase in retrograde transduction in the brain of lentiviral vectors pseudotyped with a chimeric RV-G bearing a portion of gp41 for its cytoplasmic tail (60).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study indicated that RV-G bound to an antibody transfected in a neuroblastoma cell line is targeted via early and late endosomes to lysosomes (58). In addition, lentiviral vector transduction of dendritic cells involved endosomal trafficking, and its efficiency was enhanced by suppressing autophagy (59). Indeed, we have recently reported an increase in retrograde transduction in the brain of lentiviral vectors pseudotyped with a chimeric RV-G bearing a portion of gp41 for its cytoplasmic tail (60).…”
Section: Discussionmentioning
confidence: 97%
“…It fuses with lysosomes and subsequently matures into autolysosomes, where viruses are degraded (Shoji-Kawata and Levine, 2009). Although it has been shown that autophagy aids in the degradation of other viruses in infected cells, such as vesicular stomatitis virus (VSV) (Shelly et al, 2009) and lentivector (Liu et al, 2013), no evidence has shown that autophagy is involved in the degradation process of baculoviruses in mammalian cells. Through a colocalization study using autophagosomal and lysosomal markers and a viral transduction study using the autophagy inhibitor (3-MA), we demonstrated that the autophagosome-lysosome network is, indeed, involved in the degradation process of baculoviruses during transduction.…”
Section: Discussionmentioning
confidence: 99%
“…LV were produced as previously described [25]. Briefly, 293T cells were transiently transfected with a standard calcium phosphate precipitation method.…”
Section: Methodsmentioning
confidence: 99%